1987
DOI: 10.1007/bf00052847
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes of glutathione metabolism as biochemical markers during hepatocarcinogenesis

Abstract: Enzymes of glutathione metabolism, particularly gamma-glutamyltransferase (GGT) and glutathione S-transferase (GST), play a role in multistage hepatocarcinogenesis. The enhanced expression of these enzymes in preneoplastic altered hepatic foci, nodules, and hepatocellular carcinomas has been demonstrated after treatment with a variety of initiating and promoting agents. Glutathione is necessary for the detoxification of xenobiotics and carcinogens and for cell replication. Induction of GGT in altered hepatocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 134 publications
3
27
0
Order By: Relevance
“…2004). A restoration of these enzymes following curcumin supplementation reflects the regression of a proportion of the altered hepatic foci as a result of its hepatoprotective role (Hendricvh and Pitot 1987).…”
Section: Discussionmentioning
confidence: 99%
“…2004). A restoration of these enzymes following curcumin supplementation reflects the regression of a proportion of the altered hepatic foci as a result of its hepatoprotective role (Hendricvh and Pitot 1987).…”
Section: Discussionmentioning
confidence: 99%
“…2A and C). Additionally, the chemopreventive effect of celecoxib on preneoplastic lesion development was quantified by measuring preneoplastic lesions with two markers, GGT and GST-P; both markers are considered the most sensitive for detection of altered hepatic foci induced by most chemicals [21]. In the HPT plus celecoxib group, both number and area of GGT-positive liver foci were significantly reduced by 80% (P%0.0001) and 90% (P%0.001), respectively, compared with the HPT group (Fig.…”
Section: Prevention Of Preneoplastic Lesions By Celecoxibmentioning
confidence: 99%
“…However, it is generally recognized that this immunohistochemical marker is not reactive for liver preneoplastic and neoplastic lesions of mice. It has been shown that gammaglutamyl transpeptidase (GGT) play a role in multistage hepatocarcinogenesis and the enhanced expression of this enzyme is observed in preneoplastic altered hepatocellular foci, hepatocellular adenomas, and hepatocellular carcinomas in rats and mice [13]. Therefore, GGT is used as a histochemical marker for these proliferative lesions in mice.…”
mentioning
confidence: 99%